Spatio-temporal monitoring of suspended sediments in the Solimões River (2000–2014) - Espinoza-Villar, Raúl; Martinez, Jean Michel; Armijos, E.; Espinoza, J. C.; Filizola, Naziano Pantoja; dos Santos, Andre; Willems, Bram L.; Fraizy, Pascal; Santini, William; Vauchel, Philippe (Comptes Rendus - Geoscience, 2018)
The Amazon River sediment discharge has been estimated at between 600 and 1200 Mt/year, of which more than 50% comes from the Solimões River. Because of the area's inaccessibility, few studies have examined the sediment discharge spatial and temporal pattern in the upper Solimões region. In this study, we use MODIS satellite images to retrieve and understand the spatial and temporal behaviour of suspended sediments in the Solimões River from Peru to Brazil. Six virtual suspended sediment gauging stations were created along the Solimões River on a 2050-km-long transect. At each station, field-derived river discharge estimates were available and field-sampling trips were conducted for validation of remote-sensing estimates during different periods of the annual hydrological cycle between 2007 and 2014. At two stations, 10-day surface suspended sediment data were available from the SO-HYBAM monitoring program (881 field SSS samples). MODIS-derived sediment discharge closely matched the field observations, showing a relative RMSE value of 27.3% (0.48 Mtday) overall. Satellite-retrieved annual sediment discharge at the Tamshiyacu (Peru) and Manacapuru (Brazil) stations is estimated at 521 and 825 Mt/year, respectively. While upstream the river presents one main sediment discharge peak during the hydrological cycle, a secondary sediment discharge peak is detected downstream during the declining water levels, which is induced by sediment resuspension from the floodplain, causing a 72% increase on average from June to September. © 2017 Académie des sciences
Keywords: Discharge; Hydrological Cycle; Modis; Monitoring; Radiometer; Remote Sensing; Satellite Imagery; Sediment Transport; Spatio-temporal Analysis; Suspended Sediment; Amazonas; Peru; Solimoes River